India`s energy revolution: Insights into the becoming of global power - Styczynski, Annika bose (London Routledge, 2024)
India is the third largest emitter of Greenhouse Gases which makes it an important player whose climate mitigation actions and inactions are closely scrutinised. This book studies developments in India's energy system from a governance perspective. It presents a unique compilation and synthesis of research findings that captures achievements, shortcomings, and persistent and transient challenges of India's transition towards a net-zero economy by 2070.
Keywords: Sustainable development India; Clean energy India; Energy policy India